Perbandingan Hukum Kewenangan Otoritas Jasa Keuangan Indonesia dan Jerman - Lu Sudirman; Deddy Santoso (Fakultas Hukum, Universitas Internasional Batam, 2017)
The financial system is substantial for a country , this is because the financial system will affect the stability of the economy in a country . Thus, it takes a special agency to work in the sector supervision of the financial system , namely financial services authority . However , there are still many cases faced by the financial services authority . The government has set up and run the laws and regulations regarding financial services authority which authorizes the financial services authority in maintaining economic stability with overseeing financial services . In this study, described in detail the similarities , differences , and the authority of the service , and to investigate the conditions which country is better in the authority possessed by the financial services authority . Methodology used in this research is the normative legal research -based comparative law. The data used in this study is a secondary data obtained from literature (library research). Once all the data is collected, then processed and analyzed to find the legal issues that are the object of study and conclude , then described descriptively. The results of this study indicate that Indonesia and Germany have had a pretty good authority . Indonesia and Germany have similarities and differences within its authority , the supervisory agency model of the financial services sector , the background of the establishment of the authority , scope of authority , the source of funds in carrying out its authority , and the nature of independency in the process of running the authority .